Esthetic Rehabilitation of Familial Hypodontia: A Case Report - Dali, M.; Shrestha, S.; Rajbanshi, L.K. (Birat Journal of Health Sciences, 2017)
Dental agenesis is the most common developmental anomaly in humans and is frequently associated with several other oral abnormalities. In the literature, some terms are used to describe missing teeth like oligodontia, anodontia and hypodontia. Hypodontia is the developmental absence of one or more teeth. It can be isolated or as a part of a syndrome such as in ectodermal dysplasia. The consequences of missing teeth include abnormal occlusion or altered facial appearance which can cause psychological distress in some patients. The present case report describes case of familial hypodontia in 14 years female patient with no apparent systemic abnormalities.Birat Journal of Health Sciences 2016 1(1): 71-74